Deskripsi Jumlah Leukosit dan Laju Endap Darah pada Pasien Tuberkulosis di Rumah Sakit Paru Dungus Madiun - Chalies Diah Pratiwi; Eka Puspitasari; Vivi Nurohmah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2019)
Tuberculosis is an infectious disease of global concern caused of bacterium Mycobacterium tuberculosis. It can attack lung, liver, kidneys, bones or skin. If a person infected by tuberculosis, the body will begin the mechanism of inflammation as a form of haematological manifestation. The purpose of this study was to describe the number of leukocytes and Blood Sedimentation Rate (BSR) in tuberculosis patients. The research design used is non-analytic descriptive. The population in this study were all tuberculosis patients at the Dungus Madiun Lung Hospital in 2018Using the Quota Sampling technique, the sample in this study was 30 respondents. This research was conducted on May 2018. The results of the study on tuberculosis patients showed that the number of leukocytes in TB patients was 9120 cells/µL blood, 11 (37%) patients had leukocytosis and 19 (63%) sufferers have a nominal leukocyte count. The lowest leukocyte count was 4100 cells/µL of blood and the highest was 24700 cells/µL of blood. The average value of BSR in TB patients was 71 mm/hour I, 29 (96.6%) patients experienced an increase in BSR values and 1 (3.4%) patients had normal BSR values. The lowest value of BSR is 11 mm/hour I and the highest value of BSR is 106 mm/hour I. Prevention of tuberculosis infection can be done by conducting laboratory diagnosis to find out how far the disease goes and choose the right OAT for patients. With intensive treatment, it will reduce the number of leukocytes and reduce the risk for MDR TB